2001
DOI: 10.1080/110241501317076191
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in dyspepsia

Abstract: Even in the absence of visible lesions like an ulcer, cancer or oesophagitis, patients with functional dyspepsia may complain of severe dyspeptic symptoms and have a poor quality of life. Characteristically, these patients also often have a low estimate of their own health and have complaints from several organ systems. The cause of the disease is not known. Both central nervous system and gastric disturbances appear to be involved, and their relative importance is controversial. There is no clear beneficial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Since both emotional and cognitive factors modulate stomach functions, it is not surprising that several studies have reported high scoring for anxiety and depression in some patients with FD [14Á16]. However, it is unclear whether central neural mechanisms cause the dyspeptic symptoms and reduced accommodation, or vice versa [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since both emotional and cognitive factors modulate stomach functions, it is not surprising that several studies have reported high scoring for anxiety and depression in some patients with FD [14Á16]. However, it is unclear whether central neural mechanisms cause the dyspeptic symptoms and reduced accommodation, or vice versa [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although Helicobacter pylori infection cannot explain all symptoms or ulcer cases in the upper gastrointestinal system [1], it is generally accepted that H. pylori is the most important etiologic factor leading to ulcers in the duodenum and to some extent in the stomach [2]. Furthermore, the chronic stimulation of the local immune response in H. pylori infection may lead to atrophic gastritis and even development of cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…El diagnóstico de la DF implica, por lo tanto, descartar otras enfermedades del sistema digestivo que frecuentemente tienen síntomas similares tales como la úlcera péptica, la enfermedad por reflujo gasfro-esofágico, el síndrome de colon irritable, y el cán-cer gástrico, entre otras (Berstad et al 2001;Talley et al 2000;Tack et al 2001).…”
unclassified